SHM_415480_HST_3D Thick-Butted Stone Axe - Hagaeus, Thomas; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a thick butted stone axe from the Swedish Middle Neolithic. Collected in Sweden, it is currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=991

Link to Sök I Samlingarna

https://samlingar.shm.se/object/73865BD5-A282-43BB-90E6-BACF80FF996E
Keywords: Photogrammetry; Archaeology; Archaeology; Archaeology/history; History and archaeology; Museum Object; 3D Model; Dynamic Collections; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi